Quality of Super Chilled Poultry Meat at Storage - Rathod, K.S.; Ambadkar, R. K.; Naveena, B. M. (Journal of Meat Science, 2017)
The breast meat upon exposure to super chilling (-1.5 to -2.5°C), chilled (4°C) and frozen (-18°C) temperatures up to 24 h were assessed separately for various quality attributes. The moisture content of super chilled meat (75.74+0.53) was significantly less than chilled meat (78.09+0.49). The protein content was higher in fresh meat (20.56+0.31) as compared to chilled (18.13+0.39) and super chilled meat (18.78+0.27) while fat content was not affected. The pH and water holding capacity (WHC) showed non-significant effect of cooling. There was significant (p<0.05) reduction in drip loss in super chilled meat samples as compared to chilled and frozen samples. The water activity (aw)in frozen and super chilled fillets reduced significantly (P<0.05) as compared to fresh meat. There was non-significant (p>0.05) increase in total plate count (TPC) of super chilled (4.29+0.19) and frozen fillets (4.13+0.17) whereas in chilled samples, the increase in TPC (4.69+0.23) was significant (p<0.05). However, psychrophillic (PPC) increased significantly (p<0.05) in both chilled (2.48+0.20) and super chilled fillets (1.98+0.20). The texture of super chilled fillets was comparable with chilled and frozen fillet as evident from shear force values. There was reduction in L* and b* in super chilled breast fillet against frozen and chilled fillet. Moreover, a* value increased significantly suggesting the beneficial effect of super chilling in improving the redness of breast fillet.